The suppressive properties of sheep bile against the Plasmodium chabaudi parasite in mice - M. Murshed; H.M.A. Aljawdah; M.M. Mares; S. Al-Quraishy (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT Plasmodium species are responsible for the transmission of malaria, which is still one of the most dangerous diseases to humans in the world. This study aimed to evaluate the suppressive effect of SB on parasitemia in mice infected with Plasmodium chabaudi infection. A total of 30 disease-free mice were randomly assigned to six groups. The first control non-infected group received only distilled water daily for 7 days by oral route. After being infected with 106 of P. chabaudi in the other five groups, the mice were gavaged with 0.2mL/mice of a solution containing either 25%, 50%, or 100% of SB, respectively. The fifth group orally received 10mg/ kg chloroquine phosphate (CQ). The sixth set of mice served as the infected group. Following the administration of treatments during a suppression test that lasted for five days, a daily examination of blood smears stained with Giemsa was performed. Sheep bile was able to decrease parasitemia nearly to the used reference drug, chloroquine. In addition, bile significantly decreased the diarrhea rate of infection in mice, the survival rate of mice, the parasitemia percentage, and the suppression ratio. The parasite's caused histological change was enhanced by the SB. After treatment, there was also a rise in the amounts of the liver enzymes alkaline phosphatase, aspartate aminotransferase, and alanine aminotransferase. Findings indicate that bile has antimalarial activity and can control parasitemia percentage and parasite suppression. We need further investigations to determine the mechanisms of action of the bile in vivo.